2013
DOI: 10.1038/nature12055
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the KtrAB potassium transporter

Abstract: In bacteria, archaea, fungi and plants the Trk, Ktr and HKT ion transporters are key components of osmotic regulation, pH homeostasis and resistance to drought and high salinity. These ion transporters are functionally diverse: they can function as Na + or K + channels and possibly as cation/K + symporters. They are closely related to potassium channels both at the level of the membrane protein and at the level of the cytosolic regulatory domains. Here we describe the crystal structure of a Ktr K + transporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
164
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(176 citation statements)
references
References 44 publications
11
164
0
1
Order By: Relevance
“…These residues were also the basis for matching pore helices and transmembrane helices in the earlier models. The correct alignment of the conserved selectivity filter glycine residues was confirmed by the crystal structures of TrkH and KtrB [14,15]. Mutagenesis studies with HKT and KtrB [40][41][42] showed that mutations of these glycines alter ion selectivity.…”
Section: Mutations In Putative Key Residuesmentioning
confidence: 71%
See 2 more Smart Citations
“…These residues were also the basis for matching pore helices and transmembrane helices in the earlier models. The correct alignment of the conserved selectivity filter glycine residues was confirmed by the crystal structures of TrkH and KtrB [14,15]. Mutagenesis studies with HKT and KtrB [40][41][42] showed that mutations of these glycines alter ion selectivity.…”
Section: Mutations In Putative Key Residuesmentioning
confidence: 71%
“…This helix is straight in K-channels. We wanted to exclude the possibility that this helix would also be a single straight helix in Trk1, therefore differing from the template structure [15]. The proline residues would -in case of a continued helix-represent a deviation from an optimal α-helix and could allow for function associated bending motions.…”
Section: Observed Electrostatic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these sites were located in MPM domains (MPMa: 61V/T, 68S/G, 69M/L, 77F/L, and 82L/I; MPMb: 203F/S, 208T/S, 214F/L, and 236P/G; MPMc: 363Y/S; MPMd: 443F/L and 466G/S). Finally, functional analysis outcomes with TaHKT2;1, AtHKT1;1, and rice genes suggested that site 68S/G of the MPMa domain might play a central role in determining the Na + selectivity of the transporter (Horie et al, 2001;Vieira-Pires et al, 2013). After gene duplication, paralogs went through one of four processes: in the first (nonfunctionalization) one copy initially became a pseudogene and gradually became extinct (Petrov and Hartl, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…We used the KtrAB potassium transporter from Bacillus subtilis (PDB id 4j7c) as our template (Vieira-Pires et al, 2013), which was obtained from the Protein Data Bank (http://www.pdb.org/pdb/home/home.do). Amino acid sequences were aligned with ClustalX v.1.83 (Thompson et al, 1997).…”
Section: Structural Analysismentioning
confidence: 99%